New rubber in seismic and vibration systems for insulating building structures against natural and technogeneous dynamic impact - Lysytsia, M.; Лисиця, М.І.; Lapin, V.; Лапін, В.А.; Marienkov, M.; Марєнков, М.Г.; Ahaltsov, H.; Агальцов, Г.М.; Novikova, A.; Новікова, А.В.; Kalhankov, Y.; Калганков, Є.В.; et al. (IOP Publishing, 2025)
In the article, the important aspects of improving the rubber, developed previously by M.S. Poliakov Institute of Geotechnical Mechanics, by using new chemical ingredients are considered. Of our rubber, rubber-metal elements were made and used under static and dynamic loads for over fifty years. Owing to the obtained experimental information, new optimal variant was chosen for the rubber formulation, which provides sufficient stability of the rubber and its resistance to aging. This composition of the rubber was patented in Ukraine. Further, the results of long-term tests of rubber elements in the radiation field of hard γ-radiation are presented in the paper. It is for the first time, when an important regularity is stated: aging-resistant rubber is also resistant to the action of γ-radiation, which indicates the similarity of the mechanisms of structural changes in the material.У статті розглянуто важливі аспекти вдосконалення гумового матеріалу, розробленого раніше Інститутом геотехнічної механіки ім. М.С. Полякова, шляхом використання нових хімічних компонентів. На основі цієї гуми були виготовлені гумово-металеві елементи, які застосовувалися під дією статичних і динамічних навантажень протягом понад п’ятдесяти років. Завдяки отриманим експериментальним даним було обрано новий оптимальний варіант рецептури гуми, що забезпечує достатню стабільність матеріалу та його стійкість до старіння. Цей склад було запатентовано в Україні. Додатково в роботі наведено результати тривалих випробувань гумових елементів у полі жорсткого γ-випромінювання. Вперше встановлено важливу закономірність: гума, стійка до старіння, виявляє також стійкість до дії γ-випромінювання, що свідчить про подібність механізмів структурних змін у матеріалі.
Нова гума в сейсмічних і вібраційних системах для ізоляції будівельних конструкцій від природних і техногенних динамічних впливів
Keywords: rubber; гума; аging; старіння; γ-radiation; γ-випромінювання; сhemical modification; хімічна модифікація; rubber-metal elements; гумово-металеві елементи; radiation resistance; радіаційна стійкість; rubber formulation; рецептура гуми